Penerapan Metode Design Thinking dalam Perancangan UI/UX pada Aplikasi Pintebs Kursus Online Bisnis dan Teknologi - Syukur, Moh Rezky; Muhammad, Dian; Chairuddin, Chairuddin; Herwanto, Patah (IAI Nasional Laa Roiba Bogor, 2024)
This article discusses the importance of designing user interface (UI) and user experience (UX) in mobile-based online course applications. In the introduction, the role of technology in learning, particularly online courses that enable remote learning interaction, is outlined. The literature review covers the concepts of UI, UX, and design thinking as a user-centered design methodology. The design thinking method is employed in the UI design of the online course application, encompassing the stages of empathy, problem definition, ideation, prototyping, and testing. The discussion results indicate that this approach is effective in generating UI/UX designs that align with user needs. Well-designed UI/UX facilitates user interaction and enhances their learning experience within the online course application. The conclusion of this article emphasizes the importance of user-centered UI/UX design in the development of online course applications to maximize the user's learning experience. The design thinking method has proven to be an effective approach in producing innovative designs that cater to user requirements.